2018
DOI: 10.31744/einstein_journal/2018ao4293
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grandmothers on exclusive breastfeeding: cross-sectional study

Abstract: Objective To evaluate the influence of grandmothers of infants on exclusive breastfeeding, from their perspective.Methods A descriptive cross-sectional study was carried out with 91 women from a hospital in the inland state of São Paulo. By means of a questionnaire, the following data were collected: sociodemographic data of the grandmother, mother and child; duration of exclusive breastfeeding of daughter or daughter-in-law; information on kinship of participant and grandchild; kind of help provided by grandm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 17 publications
(12 reference statements)
1
9
1
2
Order By: Relevance
“…Usually, maternal grandmothers are responsible to transfer these skills to the new mothers [ 16 ]. Evidences from a systematic review from 85 cultural contexts in 48 countries showed that grandmothers play an important role in decision making related to maternal, and child health, including pregnancy, and delivery, newborn care and breastfeeding practice [ 14 , 21 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Usually, maternal grandmothers are responsible to transfer these skills to the new mothers [ 16 ]. Evidences from a systematic review from 85 cultural contexts in 48 countries showed that grandmothers play an important role in decision making related to maternal, and child health, including pregnancy, and delivery, newborn care and breastfeeding practice [ 14 , 21 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies highlighted mixed feeding challenges, resulting in poor adherence to exclusive breastfeeding recommendations for both HIV-exposed but uninfected and HIV-unexposed children (Kinuthia et al 2010 ; Ladzani et al 2011 ; Morgan et al 2010 ; Rossouw et al 2016 ). Studies have shown that the act of mixed feeding generally occurs by providing breast milk together with water, tea and complementary food items (Swigart et al 2017 ), breast milk with pure water (Ramara, Maputle & Lekhuleni 2010 ) and tea and water in addition to breast milk (Ferreira et al 2018 ). Mixed feeding often starts as early as 1 month of age (Chaponda, Goon & Hoque 2017 ; Sibeko et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a few studies have reported that family members play an important role in influencing whether the mothers continue to breastfeed their infants. Extended families, namely grandmothers, are an important source of support for new mothers [ 31 , 32 ]. Amin et al [ 21 ] reported that almost all husbands were very supportive of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%